3h-5=9

Simple and best practice solution for 3h-5=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3h-5=9 equation:


Simplifying
3h + -5 = 9

Reorder the terms:
-5 + 3h = 9

Solving
-5 + 3h = 9

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 3h = 9 + 5

Combine like terms: -5 + 5 = 0
0 + 3h = 9 + 5
3h = 9 + 5

Combine like terms: 9 + 5 = 14
3h = 14

Divide each side by '3'.
h = 4.666666667

Simplifying
h = 4.666666667

See similar equations:

| 3h-5=9 | | 3a=180 | | 2(3x+12)=(4x+8) | | (6ab)(3b)(2)= | | 5x-3=4c+9 | | 6y^3-33y^2-63y=0 | | 25x^2+55x=-28 | | 6y^3-33y^2-63y=00 | | (8c)(c)= | | -10f-0.5=22.5 | | X+2(5)=3 | | -4-2x-x-3-9x= | | 37-9x=18+10x | | 37-9x=18+10x | | 2x+10=6x+5 | | -6x+1.2=4.2 | | 2x+10=6x+5 | | -6x+1.2=4.2 | | 500+350m=430m | | (3xy)(7z)= | | (x-5z)(7x-5z)= | | -2v+8-4=20 | | 12x^2=12x^2 | | 25-2p=-7p+p-15 | | 4c(c-3)=6-2c | | -74=-14+5k | | 5.3y+0.37=3.02y-2.48 | | (7w+4)(3w-9)=0 | | 6m^3-5m^2+-4m=0 | | 5z=4z+-12 | | -x+3=2x-6 | | -5x+4x-16+2x-6x+27= |

Equations solver categories